SymScal : metoda skalowania wielowymiarowego obiektów symbolicznych - Dudek, Andrzej; Pełka, Marcin (SymScal : Symbolic Multidimensional Scaling Method, 2008)
The aim of this paper is to present one of symbolic multidimensional scaling methods, the SymScal method along with problems which could be encountered while applying it. The article compares this method with other multidimensional scaling methods for symbolic objects. The paper presents in the empirical part the symbolic multidimensional scaling results based on LCD monitors market with the application of R programme script.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 454-461